Factors contributed to online knowledge sharing among FLP students in Faculty of Information Management / Nurul Akmar Mehat - Mehat, Nurul Akmar (2012)
The purpose of this study is to examine the contributed factors towards online knowledge sharing practice among FLP students in Faculty of Information Management. This study aims to clarify the factors based on three main elements include personal, community and technological factor. Through out the study, the most preferred electronic collaboration tools employed and the benefit of online knowledge sharing may also be presented. The quantitative method is applied for this study, combining the manual and online distribution of questionnaires to the respondents. The questionnaire is designed with both open ended and close ended questions. The study explored the online knowledge sharing factors by classifying the main element into several sub independent variables.The findings show that technological factor is the most contributed online knowledge sharing factor. As for technological factor, it is seen that perceived efficacy represent the most important influencer with the highest mean. Most respondents agree that without the technology tools, they may not successfully involve and participated in sharing knowledge virtually. It was also found that the online discussion service becomes the most preferred tool employed to perform online knowledge sharing. As for online knowledge sharing benefit, most respondents have a high consensus agreement that they share knowledge to acquire time saving benefit.